2014
DOI: 10.1002/job.1924
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from job stress: The stressor-detachment model as an integrative framework

Abstract: SummaryThis paper reviews empirical evidence on psychological detachment from work during nonwork time. Psychological detachment as a core recovery experience refers to refraining from job-related activities and thoughts during nonwork time; it implies to mentally disengage from one's job while being away from work. Using the stressor-detachment model as an organizing framework, we describe findings from between-person and withinperson studies, relying on cross-sectional, longitudinal, and daily-diary designs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

119
1,449
11
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 887 publications
(1,603 citation statements)
references
References 124 publications
(223 reference statements)
119
1,449
11
24
Order By: Relevance
“…This association as such is consistent with previous findings from variable-oriented studies (Flaxman et al, 2012;Querstret & Cropley, 2012) and compatible with the notion of energy deficiency resulting from a disrupted recovery process (Sonnentag & Fritz, 2015;Zijlstra et al, 2014). However, without the person-centred approach, we would not know that precisely the same participants who report increasing and decreasing work-related rumination, also display concurrent, corresponding changes in exhaustion.…”
Section: Exhaustion and The Profiles Of Work-related Ruminationsupporting
confidence: 91%
See 3 more Smart Citations
“…This association as such is consistent with previous findings from variable-oriented studies (Flaxman et al, 2012;Querstret & Cropley, 2012) and compatible with the notion of energy deficiency resulting from a disrupted recovery process (Sonnentag & Fritz, 2015;Zijlstra et al, 2014). However, without the person-centred approach, we would not know that precisely the same participants who report increasing and decreasing work-related rumination, also display concurrent, corresponding changes in exhaustion.…”
Section: Exhaustion and The Profiles Of Work-related Ruminationsupporting
confidence: 91%
“…Our findings concerning job demands are consistent with the stressor-detachment model, stating that job demands make it more difficult to disengage from work (Sonnentag & Fritz, 2015), as well as previous variable-oriented findings specifically on the positive relationship between job demands and work-related rumination (Berset et al, 2011;Cropley & Purvis, 2003;Querstret & Cropley, 2012;Syrek & Antoni, 2014). While previous studies have mainly examined quantitative job demands, in this study we found that cognitive and particularly emotional demands showed salient differences between the WRR classes.…”
Section: Job Demands and Leadershipsupporting
confidence: 90%
See 2 more Smart Citations
“…Particularly psychological detachment from work (i.e., not thinking about work during off-job time) has been shown to advance resource recovery (Sonnentag & Fritz, 2015). Mental detachment is important, as according to the E-R model (Meijman & Mulder, 1998) absence of work demands is a necessary condition for recovery.…”
mentioning
confidence: 99%